Demokratični domet in meje političnega pluralizma - Vasović, Vučina (Teorija in praksa, 1989)
The author discusses the relation among pluralism, socialism and democracy; the significance and possibilities of pluralism for the renaissance of democracy; the historical conditions and forms of pluralism in contemporary societies. Political science, as well as social science in general, have a task to contribute to the development of pluralist logics of socialism and to the disruption of the myth identifying pluralism and capitalism, which proves to be untrue and noxious for the theory and society. If so far in the history, capitalism has proved to have a more favourable attitude towards pluralism, this does not mean that socialism cannot change its attitude towards pluralism in the future - though considerable wisdom and good will will be required for this "turn". Contrary to several theoreticians and politicians the author considers parliamentarianism, i.e. parliament as a natural and regular framework of political pluralism, should be the final phase and instance of political decision making.
Keywords: politični pluralizem